Political management of emigration from Bangladesh in the framework of a social network theory - Shahanaz Parven (Управление)
The subject of the study is the social network theory for the management of international migration. The theory suggests that migration from the society of origin to the hosting society can occur if links exist between these two societies, and that the flow of migrants follows the established links. The theoretical prediction which one can make is that, if the political administration wishes to establish a flow of migrants between any two societies, a link between these two societies must be established first. The author tested the theory on the case of managing the emigration of workers by the government of Bangladesh. The paper found that, firstly, the links between the origin society and the host society were created artificially, however, in contrast to the theoretical forecast, the author observed that such links usually do not correspond to the geographical distribution of maximum proximity to origin or destination society. Instead, the study revealed, that the closeness of communication between two societies is generated by the proximity between political administrations of the same societies, which contradicts the theoretical expectations. In this regard, the author proposed to expand the theory of international migration in the social network, suggesting that the proximity between two political administrations, and not between two societies as a whole, is a condition necessary for international migration. This, in turn, allows us to fill a theoretical gap that is associated with the relationship between social network theory and the management of international migration. The paper concludes that it is possible to generate arbitrary migration flows, creating appropriate links between any two societies.